2015
DOI: 10.1080/20786190.2014.977033
|View full text |Cite
|
Sign up to set email alerts
|

Preventing venous thromboembolism at a district hospital: a quality improvement study

Abstract: Background: Pulmonary embolism (PE) is the most common preventable cause of hospital deaths, and almost all hospitalised patients have at least one risk factor for venous thromboembolism (VTE). Despite the availability of highly effective thromboprophylaxis in preventing VTE, numerous studies worldwide have demonstrated its under-utilisation. The aim of this study was to review and improve the utilisation of thromboprophylaxis in the prevention of VTE in hospitalised patients at Oudtshoorn district hospital, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Numerous interventions have been proposed to improve VTE prophylaxis prescription, such as electronic alert systems, an opt-out thromboprophylaxis policy, performance evaluation and feedback, as well as practitioner education. [13][14][15][16][17] Although electronic prescription alerts and performance reviews are not be feasible in our setting, the inclusion of a risk assessment sheet on the inpatient prescription charts and providing continuous practitioner education are interventions that should be considered for improving VTE prophylaxis prescription. With such a high percentage of patients at risk, an opt-out policy of thromboprophylaxis prescription should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous interventions have been proposed to improve VTE prophylaxis prescription, such as electronic alert systems, an opt-out thromboprophylaxis policy, performance evaluation and feedback, as well as practitioner education. [13][14][15][16][17] Although electronic prescription alerts and performance reviews are not be feasible in our setting, the inclusion of a risk assessment sheet on the inpatient prescription charts and providing continuous practitioner education are interventions that should be considered for improving VTE prophylaxis prescription. With such a high percentage of patients at risk, an opt-out policy of thromboprophylaxis prescription should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In Togo, it was less than 07 days [14]. Compliance with the recommendations in our contexts seems to come up against several obstacles including: the high cost and the unavailability of treatment resources, the lack of a thromboprophylaxis practice protocol, the difficulties in identifying patients at risk, insufficient knowledge of the recommendations in this area [10] [13] [14] [16]. A South African study evaluating the impact of communication for improving the practices of health professionals has shown that it allows a significant increase in the frequency of thromboprophylaxis in patients at risk, which increased from 4.6% to 36% [16].…”
Section: Discussionmentioning
confidence: 99%
“…Compliance with the recommendations in our contexts seems to come up against several obstacles including: the high cost and the unavailability of treatment resources, the lack of a thromboprophylaxis practice protocol, the difficulties in identifying patients at risk, insufficient knowledge of the recommendations in this area [10] [13] [14] [16]. A South African study evaluating the impact of communication for improving the practices of health professionals has shown that it allows a significant increase in the frequency of thromboprophylaxis in patients at risk, which increased from 4.6% to 36% [16]. In addition, studies support that the development of outpatient surgery and rapid rehabilitation after surgery (RRAS) has a positive impact on the efficacy of postoperative pharmacological thromboprophylaxis and would reduce its duration and therefore the cost of treatment [1].…”
Section: Discussionmentioning
confidence: 99%